The Globalization of Cultural Eutrophication in the Coastal Ocean: Causes and Consequences - Malone, Thomas C.; Newton, Alice (Frontiers in Marine Science, 2020)
Coastal eutrophication caused by anthropogenic nutrient inputs is one of the greatest threats to the health of coastal estuarine and marine ecosystems worldwide. Globally, ∼24% of the anthropogenic N released in coastal watersheds is estimated to reach coastal ecosystems. Seven contrasting coastal ecosystems subject to a range of riverine inputs of freshwater and nutrients are compared to better understand and manage this threat. The following are addressed: (i) impacts of anthropogenic nutrient inputs on ecosystem services; (ii) how ecosystem traits minimize or amplify these impacts; (iii) synergies among pressures (nutrient enrichment, over fishing, coastal development, and climate-driven pressures in particular); and (iv) management of nutrient inputs to coastal ecosystems. This comparative analysis shows that “trophic status,” when defined in terms of the level of primary production, is not useful for relating anthropogenic nutrient loading to impacts. Ranked in terms of the impact of cultural eutrophication, Chesapeake Bay ranks number one followed by the Baltic Sea, Northern Adriatic Sea, Northern Gulf of Mexico, Santa Barbara Channel, East China Sea, and the Great Barrier Reef. The impacts of increases in anthropogenic nutrient loading (e.g., development of “dead zones,” loss of biologically engineered habitats, and toxic phytoplankton events) are, and will continue to be, exacerbated by synergies with other pressures, including over fishing, coastal development and climate-driven increases in sea surface temperature, acidification and rainfall. With respect to management, reductions in point source inputs from sewage treatment plants are increasingly successful. However, controlling inputs from diffuse sources remains a challenging problem. The conclusion from this analysis is that the severity of coastal eutrophication will likely continue to increase in the absence of effectively enforced, ecosystem-based management of both point and diffuse sources of nitrogen and phosphorus. This requires sustained, integrated research and monitoring, as well as repeated assessments of nutrient loading and impacts. These must be informed and guided by ongoing collaborations among scientists, politicians, managers and the public.